Ambient Pyrethroid Pesticide Exposures in Adult Life and Depression in Older Residents of California's Central Valley. Issue 6 (2nd December 2020) - Furlong, Melissa A.; Paul, Kimberly C.; Cockburn, Myles; Bronstein, Jeff; Keener, Adrienne; Rosario, Irish Del; Folle, Aline Duarte; Ritz, Beate
Abstract : Pyrethroid pesticide exposures may be associated with the onset of depression in later life via disruption of dopaminergic, serotonergic, and neurological functioning. We sought to investigate the association between living near agricultural pyrethroid pesticide applications and depression measures in central California, using two waves (PEG 1&2, total N = 1, 654) of a case control study of Parkinson's disease (PD). At enrollment, participants self-reported history of use of depression medications and dates of MD-diagnosed depression and anxiety. Participants also completed a Geriatric Depression Scale-Short Form upon enrollment. We used the California Pesticide Use Registry to assign estimated ambient pyrethroid pesticide exposures at participant's home addresses over the 5 years before the index date (date of outcome, or an age-matched year for participants without the outcome). We used logistic and linear regression to evaluate associations between living near any pyrethroid applications over the 5-year index period and measures of depression and anxiety. We also evaluated modification by study wave and PD status. We observed associations of pyrethroids with depression, depression medications, and anxiety (adjusted odds ratio [aOR] depression = 1.54, 95% confidence interval [CI] 1.14, 2.07; aOR depression medications = 1.68, 95% CI 1.25, 2.25; aOR anxiety = 1.60, 95% CI 1.17, 2.18). However, we observed no associations with mild/moderate depressive symptoms according to the GDS score at enrollment (aOR = 1.04, 95% CI 0.77, 1.42). We did not observe a consistent modification of the pyrethroid-depression associations by study wave and PD status. Ambient pyrethroid pesticide exposures may be associated with measures of depression in later life.